Design of an Automatic Device for Watering Jasmine Flower Plants Using a Soil Based Moisture Sensor Arduino Microcontroller - Nanang (Jurnal Inotera, 2024)
The In everyday life, watering plants is a very important factor in maintaining and caring for jasmine plants. Water itself is a basic resource that supports the life needs of jasmine plants. If there is no water, the growth of jasmine flowers will be hampered, and the plant can even die. In general, watering plants is done conventionally, this is considered impossible to do in a short time, not to mention when the plant owner is far from where the plants are. In this case, an automatic device for watering jasmine plants was created using a pump controlled by the Arduino Uno, as well as using a soil moisture sensor to provide analog data to the Arduino Uno to regulate the on and off of the water pump based on the humidity that has been set and the use of the LCD module. I2C to display soil moisture, to make it easier for jasmine plant lovers to care for their plants in terms of watering. This research method was adopted from the prototype development method. The results of this research are that the pump can water plants when the humidity is < 30%, and the pump stops watering when the humidity is > 50%.